Gruppenaufnahme
Bundeskanzler Helmut Schmidt; Bundesinnenminister Werner Maihofer; Bundespostminister Kurt Gscheidle; CDU-Vorsitzender Helmut Kohl; CSU-Vorsitzender Franz Josef Strauß; Vorsitzender CDU/CSU-Bundestagsfraktion Helmut Kohl; CSU-MdB Franz Josef Strauß;Kommandeur der GSG 9 Ulrich Wegener; Stewardess Gabriele Dillmann;